The formal system and its role in Intellectual construction of interior spaces (Journal of the College of Basic Education, 2022)
There are many aspects that dealt with the concept of form spatially, and differed according to the prevailing philosophies and intellectual orientations, and to study the form in interior design in all its intellectual aspects, it is necessary to study its sources, properties, and the interrelationship between it and the function performed and the meaning, as the form is inseparable from its intellectual meaning as it embodies the two sides of the utilitarian and aesthetic design in integration and synergy.Creative ideas are a vision resulting from the ability and ability of the interior designer to maneuver with vocabulary and elements through his use of form in new contexts to communicate a specific meaning, and to find a new function, which in turn becomes a latent force that excites the recipient.